Dimensi Prajñā Pāramitā Hṛdaya Sūtra Dalam Logika Kontradiksi Diri Absolut Nishida Kitarō - Nur Fattah, Galuh (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
This research article explains the connections and similarities regarding the logical structure in the Prajñā Pāramitā Hṛdaya Sūtra and Nishida Kitarō's logic of absolute self-contradiction. Essentially the Prajñā Pāramitā Hṛdaya Sūtra teaches about nothingness or Sunyata. Nothingness in logic of absolute self-contradiction is called zettai mu. In Prajñā Pāramitā Hṛdaya Sūtra, the teaching about nothingness is explained through a logic scheme of negation or can be said to be the logic of inversion. On the other hand, Nishida Kitarō's logic of absolute self-contradiction also shows the same thing, it can be seen as a logical scheme which is defined as the logic of exception without exception (mufunbetsu no funbetsu) or can also be understood as a point of view without point of view (tachiba naki tachibai) . This logic can be understood as paradoxical logic or paralogism (hairi no ri). The concept of Sunyata in the Prajñā Pāramitā Hṛdaya Sūtra is basically a mental state that leads to Nirvana, whereas, zettai mu in Nishida Kitarō's logic of absolute self-contradiction, leads to the highest understanding without any discrimination. Overall it can be concluded that in the logic of absolute self-contradiction there are identical dimensions of the Prajñā Pāramitā Hṛdaya Sūtra, but based on the criticism given by Hakuin and Tsujimura, the core thing in the Sūtra , namely nothingness, needs to be redefined properly and its true meaning understood.